The Role of Social Media Usage in Promoting Organizational Citizenship of Teachers Behavior in Private Schools in Capital Amman - Lubna Ali Ataallah Al salaymeh, Prof. Ahmed F. Abukaream, (Opción)
The study aimed at identifying the role of social media in promoting organizational citizenship behavior among teachers. In order to Achieve the objective of this study, the descriptive associative approach has been applied on as ample consisted of (254) School Mangers who works in private schools of Capital Amman, the study used A questionnaire of 3 items Altruism, civility and organizational behavior distributed on (30) questions. The validity and reliability of the study has been verified and secured. Furthermore, the findings of the study showed the degrees of practicing ethical leadership and organizational commitment was moderate, and no statistically significant differences were found due both service period and scientific qualification. The study recommended the need to increase awareness of the importance of the role of media to enhance organizational citizenship behavior, and encourage school principals to take advantage of social media and employ it positively in the educational process, which is reflected in strengthening the organizational behavior of teachers and staff.